رصد جودة المياه الجوفية لبعض الآبار المستثمرة في منطقة الساحل السوري (حريصون – بانياس) - جنيدي, حسين علي; صقر, إبراهيم عزيز; الدركون, علا مالك (Latakia University Journal -Biological Sciences Series, 2014)
نظراً لخطورة التلوث الكيميائي عموماً وفي الآبار الارتوازية ضمن المناطق الزراعية المأهولة خصوصاً، تم تنفيذ دراسة علمية من أجل تحديد تراكيز بعض الشوارد في مياه الآبار الموزعة ضمن منطقة حريصون إضافة لرصد التغيرات في قيمها كمؤشر على معدل التلوث الكيميائي في منطقة الدراسة بفعل الأنشطة القائمة . تضمن البحث إجراء تحاليل دورية شهرية فيزيائية وكيميائية لآبار مستثمرة في منطقة حريصون التابعة لمدينة بانياس على مدى عام كامل بدءاً من شهر أيلول 2011 حتى شهر آب 2012 وذلك عن طريق اختيار عشرة آبار مستثمرة موزعة في المنطقة . شملت الدراسة التغيرات التي تطرأ على كل من درجة الحرارة والرقم الهيدروجيني والناقلية الكهربائية و مجموعة الشوارد السالبة ( النترات NO3-، الفوسفات PO43-، الكبريتات SO42-، الكلوريد Cl- ) بالإضافة إلى الشوارد الموجبة ( الأمونيوم NH4+، الصوديوم Na+ ). لقد أظهرت القيم التي تم الحصول عليها للشوارد المدروسة تفاوت واضح بين شهر وآخر للعينات المأخوذة من نفس الآبار، ويعود ذلك لجملة النشاطات الزراعية والبشرية وإلى الظروف المناخية التي سادت خلال مواعيد أخذ العينات. تبين النتائج المسجلة حصول حالات تلوث كيميائي في مياه الآبار المدروسة غير مطابقة المواصفة القياسية السورية لمياه الشرب(لعام 2011-2012) تنذر بالكثير من المخاطر الصحية والبيئية، خصوصاً أن الكثير من تلك الآبار تستخدم لأغراض الشرب. According to the chemical pollution danger in general and its danger on groundwater wells in agricultural areas particularly the inhabited ones , the scientific study was implemented to determine the concentrations of some ions in water wells within the area of Hraesoon; In addition to, monitoring their changing values which indicate the rate of chemical pollution in the study area due to existing activities. The search involves a monthly periodic physical and chemical analyzes in the invested wells in Hraesoon area , Banias city for a whole year. starting from September 2011 till August 2012 by choosing ten invested wells disterbuted in the area. The study includes the changing of temperature ,pH, electrical conductivity, and the group of negative ions (nitrate NO3-, phosphate PO43-, sulphates SO42-, chloride Cl-) in addition to positive ions (ammonium NH4 +, Sodium Na +). The values of the studied ions have demonstrated ​​ a clear disparity in each month for the samples taken from the same wells, due to the agricultural ,human activities and climatic conditions that prevailed during the sampling dates. The recorded results show cases of chemical contamination in the water wells studied not identical the Syrian standard for drinking water (2011-2012) portend a lot of health and environmental risks, especially that many of those wells are used for drinking purposes.